ELF-1 expression in nasopharyngeal carcinoma facilitates proliferation and metastasis of cancer cells via modulation of CCL2/CCR2 signaling - Chen CH; Su LJ; Tsai HT; Hwang CF (Cancer Management and Research, 2019)
Chang-Han Chen,1,2 Li-Jen Su,3–5 Hsin-Ting Tsai,1 Chung-Feng Hwang6,71Guangdong Institute of Gastroenterology, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangzhou, 510020, People’s Republic of China; 2Department of Applied Chemistry, Graduate Institute of Biomedicine and Biomedical Technology, National Chi Nan University, Nantou, 54561, Taiwan; 3Department of Biomedical Sciences and Engineering, College of Health Sciences and Technology, National Central University, Taoyuan City, Taiwan; 4Education and Research Center for Technology Assisted Substance Abuse Prevention and Management, Taoyuan City, Taiwan; 5IHMed Global, Taipei City, Taiwan; 6Department of Otolaryngology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 7Kaohsiung Chang Gung Head and Neck Oncology Group, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung 83301, TaiwanBackground: Nasopharyngeal carcinoma (NPC) is a prevalent malignant tumor in Southeast Asia. The management of NPC has remained a challenge until now. ELF-1 is a member of the ETS family of transcription factors that regulate genes involved in cellular growth. ELF-1 expression has been reported in various cancers and is required for tumor growth and angiogenesis; however, its function in NPC remains unclear. In the present study, we characterized the role and underlying mechanism of ELF-1 in NPC.Methods: The biological functions of ELF-1 in NPC cells such as proliferation, migration, invasion, and drug resistance were investigated using MTT, BrdU incorporation, and Transwell assays. To gain more insight into the mechanism of ELF-1 in NPC, we analyzed CCL2/CCR2 signaling by Western blotting, ELISA, siRNAs, and CCR2 antagonist.Results: Gain-of-function of ELF-1 in TW01 and TW04 cells promoted NPC cell proliferation, BrdU incorporation, migration, invasion and cisplatin resistance. By contrast, knockdown of ELF-1 produced opposite results. Overexpression of ELF-1 enhanced the expression of CCL2 via binding to its promoter region and increased the level of the extracellular matrix protein CCL2 in cell culture medium. ELF-1 expression also modulated the downstream targets of CCL2/CCR2 signaling. Most importantly, ELF-1-induced NPC malignant phenotypes were abrogated by a CCR2 inhibitor, implying that the CCL2/CCR2 signaling axis was involved in ELF-1-mediated regulation in NPC.Conclusion: Our data suggest that ELF-1 plays an oncogenic role in NPC development associated with the CCL2/CCR2 signaling pathway and may therefore be a potential target for NPC therapy.Keywords: ELF-1, NPC, CCL2